The Black Album - Beatrice, Luca; Bertocchi, Davide; Botto & Bruno; Caprio, Nicola Di; Carcano, Laura; Carlo, Claudio Di; Ellis, Patricia; Guarnaccia, Matteo; Harding, Leeta; Leoni, Chiara; Morey, Joan; Paparoni, Demetrio; et al. (Milano : Antonio Colombo Arte Contemporanea Milano, 2004)
Abbominevole ; Bertocchi, Davide ; Bijl, Marc ; Bloody Riot - Roberto Perciballi ; Botto & Bruno ; Carlo, Claudio Di ; Caprio, Nicola Di ; Grassl, Claudia ; Guarnaccia, Matteo ; Harding, Leeta ; Hipwell, Philip ; King, Scott ; Kirchhoff, Thorsten ; Mastrovito, Andrea ; Melgaard, Bjarne ; Migliore, Bartolomeo ; Morey, Joan ; Ozmo ; Parker, Erik ; Pettena, Robert ; Pettibon, Raymond ; Presicce, Luigi ; Prof. Bad Trip ; Roig, Bernardi ; Schumann, Christian ; Sedda, Gabriele ; Starr, Georgina ; Templeton, Ed ; Vetrugno, Maurizio
Engels
Italiaans
Exhibition. The Black Album. Antonio Colombo Arte Contemporanea Milano, 27.05.2004 - 16.07.2004.
boek